Enhancement of agri-food by-products: green extractions of bioactive molecules with fungicidal action against mycotoxigenic fungi and their mycotoxins - Giorni, Paola; Bulla, Giulia; Leni, Giulia; Soldano, Mariangela; Tacchini, Massimo; Guerrini, Alessandra; Sacchetti, Gianni; Bertuzzi, Terenzio (Frontiers in Nutrition, 2023)
Introduction Today, alternative strategies based on the use of bioactive compounds have been proposed to reduce mycotoxin contamination and limit the use of chemical fungicides. Methods In the present work, several by-products collected from the agri-food chain (i.e., red and white grape marc, red grapevine leaves, grape seeds and stalks, pear, apple, green beans, tomato, and spent hops) were subjected to green extraction protocols (i.e., steam distillation, Ultrasound-Assisted, and Naviglio® extraction) to obtain extracts rich in polyphenols and terpenes. Each extract was assessed in vitro for its ability to inhibit the development of the main mycotoxigenic species and related mycotoxins. Results and Discussion Aspergillus flavus and A. carbonarius were significantly reduced by pear (from −45 to −47%) and grape marc (from −21 to −51%) extracts, while F. graminearum was shown to be highly influenced by grape stalk, pear, and grape marc extracts (−24% on average). On the contrary, F. verticillioides was inhibited only by pear (−18%) and to a very low and negligible extent by apple (−1%) and green beans (−3%). Regarding the reduction of mycotoxins, the extracts were able to inhibit OTA from 2 to 57%, AFB1 from 5 to 75%, and DON from 14 to 72%. The highest percentages of reduction were obtained against FBs (from 11 to 94%), ZEN (from 17 to 100%), and Alternaria toxins (from 7 to 96%). In conclusion, this work provided promising results for the production of bioactive extracts obtained from agri-food by-products, which could be exploited as potential biofungicides against the development of mycotoxigenic fungi and related mycotoxins.